Biomarkers approach in the diagnosis and prognosis of sepsis - Mahnaz, Irani-Shemirani (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Sepsis is a systematic host response to infection defined by suppression of the immune system and organ failure which can rapidly lead to septic shock and death if not managed properly. Methods Therefore, the timely diagnosis of sepsis has prompted researchers to assess several number of blood biomarkers. In a complex situation like sepsis where multiple organs and systems are involved, the sensitivity and specificity of blood indicators that can easily and accurately show the severity and prognosis of the disorder are of great importance. Results C-reactive protein (CRP) and Procalcitonin are the most common biomarkers used in clinical routine to diagnose sepsis and monitor the response to treatment. Other biomarkers including pro-inflammatory and anti-inflammatory cytokines and chemokines, monocyte and lymphocyte, antibodies, and nucleic acid can also be used to assess the disorder. Biomarkers offer utility for disease progress, the prognosis of disorder, risk stratification, and treatment effect rather than diagnosis at the early stage of sepsis. Conclusions Therefore, although defining molecular properties in septic patients opens up new means to diagnose and manage sepsis in a shorter time compared to conventional methods currently used at hospitals, further clinical evaluation of biomarkers should be performed. In this review, we summarized pathophysiology, pathogeneses, and clinical diagnosis of sepsis. We also provided an overview of the role of candidate biomarkers on diagnosis and prognosis of sepsis.